Cover Feature: Hydrothermal Crystallization of Nano‐Titanium Dioxide for Enhanced Photocatalytic Hydrogen Generation (ChemPhotoChem 9/2018). Issue 9 (22nd August 2018) - Kundu, Simanta; Polshettiwar, Vivek
Abstract : The Cover Feature shows how the chemistry of morphology‐controlled nanomaterials and hydrothermal crystallization techniques can be combined to convert amorphous TiO2 sites into highly active TiO2 sites to tune the photocatalytic activity of hybrid photocatalysts. More information can be found in the Communication by S. Kundu and V. Polshettiwar onpage 796 in Issue 9, 2018 (DOI:10.1002/cptc.201800101 ).